2021
DOI: 10.1002/anie.202106743
|View full text |Cite
|
Sign up to set email alerts
|

Unravelling the Hydration Barrier of Lignin Oleate Nanoparticles for Acid‐ and Base‐Catalyzed Functionalization in Dispersion State

Abstract: Lignin nanoparticles (LNPs) are promising renewable nanomaterials with applications ranging from biomedicine to water purification. However, the instability of LNPs under acidic and basic conditions severely limits their functionalization for improved performance. Here, we show that controlling the degree of esterification can significantly improve the stability of lignin oleate nanoparticles (OLNPs) in acidic and basic aqueous dispersions. The high stability of OLNPs is attributed to the alkyl chains accumula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
50
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 44 publications
(61 citation statements)
references
References 67 publications
(91 reference statements)
2
50
0
Order By: Relevance
“…Due to a high number of accessible functional groups on the surface of LNPs, as shown also in this study, LNPs can be easily modified to carry small and large molecules (proteins, chemotherapy, genotherapy, etc.). For instance, the hydration barrier and the ability for acid and base-catalyzed surface modifications of lignin oleate NPs have been recently described in a study by Moreno et al (2021).…”
Section: Lignin Nanoparticles In Comparison To Other Nanocomposites U...mentioning
confidence: 99%
“…Due to a high number of accessible functional groups on the surface of LNPs, as shown also in this study, LNPs can be easily modified to carry small and large molecules (proteins, chemotherapy, genotherapy, etc.). For instance, the hydration barrier and the ability for acid and base-catalyzed surface modifications of lignin oleate NPs have been recently described in a study by Moreno et al (2021).…”
Section: Lignin Nanoparticles In Comparison To Other Nanocomposites U...mentioning
confidence: 99%
“…The LNPs could be rapidly regenerated to the original spherical shape upon switching pH, suggesting the excellent reversibility and controllability of the LNPs fabrication (Figure 3). Although some previous studies determined that the high stability of LNPs at different pH environments can be beneficial for their retention and large‐scale production, [6b,15b,18] the rapid and reversible fabrication of LNPs opens a new route for lignin valorization.…”
Section: Resultsmentioning
confidence: 99%
“…showed that particles analogous to LNPs, but prepared using lignin oleate, contain a hydration barrier layer resulting from the hydrophobic acyl chains that hinder protonation and deprotonation of carboxylic acid and phenolic hydroxyl groups under acidic and alkaline conditions. 374 The OLNPs (oleiclignin nanoparticles) were surface-modified without any crosslinking directly in aqueous dispersions using epoxy ringopening reactions at pH 2 and pH 12. The resulting methacrylated and cationized particles showed competitive performance as curable anticorrosion coatings and pH-controlled switchable cationic/anionic adsorbents for rapid water purification.…”
Section: Carbon-lignin Hybridsmentioning
confidence: 99%